Tras el silencio - Cury Abril, Mónica (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
The intervention from the Art therapy as a space of elaboration of the traumatic fact favours the victim’s recovery and facilitates its social reinsertion and its therapeutic rehabilitation through the image and the creative process. It promotes the expression from a different language that allows the canalization of sensations, emotions and memories without pushing to the catharsis. Art therapy offers a new road of expression that eliminates in great measure the limitation of the verbal blockade. It allows capture through the plastic image the sensorial reminiscent images, favouring the memory and the construction of a coherent story that facilitates the understanding of the traumatic event. This understanding opens for the victim the possibility to integrate the experience like a personal history whit a beginning, a development and a final. In a sure and free of trials space that facilitates the intervention from the salutogenesis, recognizing the strategies of survival and their implication in the processes health / illness.